Implementasi Workflow Automation Menggunakan N8N Pada Sistem Helpdesk Teknologi Informasi Untuk Meningkatkan Efisiensi Penanganan Tiket - Han Sulaiman; Michael Sonny (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Information Technology (IT) helpdesk services play a crucial role in supporting organizational operations by handling incidents, service requests, and user complaints. However, manual ticket handling processes often result in delayed responses, inefficient information distribution, and increased administrative workload. This study aims to implement workflow automation using n8n to improve the efficiency of IT helpdesk ticket handling. The Prototype development method was adopted, consisting of requirement analysis, workflow design, prototype implementation, system testing, and evaluation. The proposed system integrates a Laravel-based helpdesk application, MySQL database, REST API, n8n as the workflow automation engine, Telegram Bot for technician notifications, and Gmail SMTP for email services. System functionality was evaluated using Black Box Testing on ticket submission, ticket ID generation, database storage, notification delivery, and ticket status updates. The results demonstrate that all system functions operated successfully and automated the ticket management process effectively. The implementation reduced manual administrative tasks, accelerated information delivery, improved real-time ticket monitoring, and enhanced overall operational efficiency. These findings indicate that n8n provides an effective low-code and open-source solution for automating IT helpdesk services and improving organizational service performance.